Characterization of bladder and external urethral activity in mice with or without spinal cord injury—a comparison study with rats - Kadekawa, Katsumi (Am J Physiol Regul Integr Comp Physiol, 2016)
To clarify the lower urinary tract function in mice, we compared bladder and urethral activity between rats and mice with or without spinal cord injury (SCI). Female Sprague-Dawley rats and C57BL/6N mice were divided into five groups: 1) spinal intact (SI) rats, 2) SI mice, 3) pudendal nerve transection (PNT) SI mice, 4) spinal cord injury (SCI) rats, and 5) SCI mice. Continuous cystometry (CMG) and external urethral sphincter (EUS)-electromyogram (EMG) analyses were conducted under an awake, restrained condition. During voiding bladder contractions, SI animals exhibited EUS bursting with alternating active and silent periods, which, in rats but not mice, coincided with small-amplitude intravesical pressure oscillations in CMG recordings. In SI mice with bursting-like EUS activity, the duration of active periods was significantly shorter by 46% (32 ± 5 ms) compared with SI rats (59 ± 9 ms). In PNT-SI mice, there were no significant differences in any of cystometric parameters compared with SI mice. In SCI rats, fluid elimination from the urethra and the EUS bursting occurred during small-amplitude intravesical pressure oscillations. However, SCI mice did not exhibit clear EUS bursting activity or intravesical pressure oscillations but rather exhibited intermittent voiding with slow large-amplitude reductions in intravesical pressure, which occurred during periods of reduced EUS activity. These results indicate that EUS pumping activity is essential for generating efficient voiding in rats with or without spinal cord injury. However, EUS bursting activity is not required for efficient voiding in SI mice and does not reemerge in SCI mice in which inefficient voiding occurs during periods of reduced tonic EUS activity.